RFID Personnel Control System That Can Be Managed Via 4.5G - Abdülkadir ÇAKIR; Halil KAYGISIZ (Indonesian Journal of Electrical Engineering and Computer Science, 2016)
The current study aimed to reveal that personnel control by the employer should be conducted using Radio Frequency Identification (RFID) technology in an easier and more modular way. The most important feature differentiating the RFID from the existing technologies is that it works wirelessly. The hardware used in the study can be managed via Ethernet port. In this study, it is ensured that data be transmitted via Internet by using a mobile cellular communication system. The control of the set up system can be conducted wirelessly via any environment in which an Internet connection can be established. Thanks to the created system, information about arrival and departure dates of the places to where the mobile personnel should go can be monitored 24/7 from anywhere that has internet connection. As a result of the tests and applications that have been conducted, it has been seen that the data could not be transmitted in a radio-frequency environment because of the error caused by the RFID tag. As a result of the calculations made after the application, it has been put forward that the error margin is 7±1%.